Injection-molded lightweight and high electrical conductivity composites with microcellular structure and hybrid fillers. Issue 5 (September 2019) - Tian, Sheng; Dong, Binbin; Guo, Yahao; Zhao, Can; Zhang, Mengxia; Xiao, Mengjun
Polypropylene/carbon black (PP/CB) and PP/CB/multiwalled carbon nanotube (PP/CB/MWCNT) composites were fabricated by solid and foam injection molding, with the goal of enhancing the electrical conductivity of the composites while decreasing the cost of the final product. The foaming behavior and through-plane (T-P) electrical conductivity of the composites were characterized and analyzed. Cell growth increased the interconnection of the conductive fillers, changed the filler orientation, and enhanced the T-P electrical conductivity of the composites. Under appropriate processing conditions (200°C melt temperature, 70 cm 3 /s injection flow rate, and 5% void fraction), the T-P electrical conductivity of the foam PP/CB composites was 5 orders of magnitude higher than that of the solid composites (from 5.877 × 10 −12 S/m to 1.010 × 10 −7 S/m). Moreover, the T-P electrical conductivity values of the PP/CB and PP/CB/MWCNT were compared at the same conductive fillers content (15 wt%). The results showed that the T-P electrical conductivity of the PP/CB/MWCNT composites was far higher than that of the PP/CB composites by almost five orders of magnitude because the MWCNT acted as a bridge between CB particles, and a unique geometric shape was formed in the system. The T-P electrical conductivity of the foam PP/CB/MWCNT composites with 15 wt% carbon fillers was higher than that of the solid PP/CB composites with 20 wt% carbon fillers. This study reveals that the effect of foaming and the addition of hybrid fillers can improve the T-P electrical conductivity of plastic products, which is very important for the development of lightweight conductive plastics.